Racial disparities in inpatient clinical presentation, treatment, and outcomes in brain metastasis. Issue 1 (31st July 2022) - McCray, Edwin; Waguia, Romaric; de la Garza Ramos, Rafael; Price, Meghan J; Williamson, Theresa; Dalton, Tara; Sciubba, Daniel M; Yassari, Reza; Goodwin, Andrea N; Fecci, Peter; Johnson, Margaret O; Chaichana, Kaisorn; et al.
Abstract: Background: Few studies have assessed the impact of race on short-term patient outcomes in the brain metastasis population. The goal of this study is to evaluate the association of race with inpatient clinical presentation, treatment, in-hospital complications, and in-hospital mortality rates for patients with brain metastases (BM). Method: Using data collected from the National Inpatient Sample between 2004 and 2014, we retrospectively identified adult patients with a primary diagnosis of BM. Outcomes included nonroutine discharge, prolonged length of stay (pLOS), in-hospital complications, and mortality. Results: Minority (Black, Hispanic/other) patients were less likely to receive surgical intervention compared to White patients (odds ratio [OR] 0.70; 95% confidence interval [CI] 0.66–0.74, p < 0.001; OR 0.88; 95% CI 0.84–0.93, p < 0.001). Black patients were more likely to develop an in-hospital complication than White patients (OR 1.35, 95% CI 1.28–1.41, p < 0.001). Additionally, minority patients were more likely to experience pLOS than White patients (OR 1.48; 95% CI 1.41–1.57, p < 0.001; OR 1.34; 95% CI 1.27–1.42, p < 0.001). Black patients were more likely to experience a nonroutine discharge (OR 1.25; 95% CI 1.19–1.31, p < 0.001) and higher in-hospital mortality than White (OR 1.13; 95% CI 1.03–1.23, p = 0.008). Conclusion: Our analysis demonstrated that race is associated with disparate short-term outcomes in patients with BM. More efforts are needed to address these disparities, provide equitable care, and allow for similar outcomes regardless of care.